Could Selectively Skipping of the Repetitive Thinking Questionnaire among a Series of Self-Report Scales in a Study Be a Coping Strategy? - Ý. Volkan GÜLÜM; Ýhsan DAÐ (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Depending on an observation in which some of the subjects’ nonrandom irresponsiveness to repetitive thinking questionnaire items among fully answered others in a study of current researchers, the aims of the present study were to test that whether the ignorance of repetitive thinking items is a stress coping strategy or not, to compare people who ignore the repetitive thinking items (IRT) with people who have high repetitive thinking (HRT) and low repetitive thinking (LRT) in context of attachment patterns, sychopathological symptoms and cognitive flexibility. Method: 432 (278 women and 154 men) college students were selected from a larger research project sample pool which had funded by TÜBÝTAK. Participants were divided into three groups according to their repetitive thinking conditions (ignorance, high and low score). All participants have completed the Experiences in Close Relationships – Revised Inventory, Repetitive Thinking Questionnaire, Cognitive Flexibility Inventory and Brief Symptom Inventory. Results: To test our hypothesis series of ANOVA, MANOVA and discriminant analysis were conducted. According the variance analysis, the IRT group had more psychopathology symptoms and attachment anxiety than the LRT group and less than the HRT group. The IRT group had more cognitive flexibility than the HRT group and less than the LRT group. According to discriminant analysis, the LRT and IRT groups had been distinguished the HRT group in the context of psychopathology symptoms and attachment anxiety; the LRT and HRT groups had been distinguished the IRT group in the context of cognitive flexibility-control dimension. Conclusion: According to the results, the ignorance of the repetitive thinking items may be a defensive mechanism or stress coping strategy. (Journal of Cognitive Behavioral Psychotherapy and Research 2013, 2: 89-97) [JCBPR 2013; 2(2.000): 89-97]